2021
DOI: 10.32615/bp.2020.172
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of double-stranded RNA molecules deriving from Tomato yellow leaf curl virus reduces cognate virus infection in tomato

Abstract: Tomato yellow leaf curl virus (TYLCV), a whitefly-transmitted single-stranded DNA (ssDNA) virus, causes the most important viral disease of tomato worldwide. TYLCV-mediated disease is mainly controlled via extensive insecticide sprays aiming at the whitefly vector. RNA-based vaccination was proven to be a non-transgenic approach leading to efficient plant virus control. In this work, double-stranded RNA (dsRNA) molecules deriving from sequences of the C4 and V2 genes of TYLCV-Mild were produced in vitro and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…To date, the studies on the topical application of dsRNA have been conducted against at least 14 plant viruses having positive sense ssRNA as their genome ( Taliansky et al, 2021 ). To some extent, the approach was also found to be effective against ssDNA virus (genus Begomovirus ), however, not much information is available as only three studies are available that showed limited or no effect against Begomovirus ( Namgiala et al, 2019 ; Rego-Machado et al, 2020 ; Melita et al, 2021 ). Recently, two studies had shown the efficacy of topically applied dsRNA against the type member of the genus Orthotospovirus , TSWV, a negative/ambisense ssRNA virus ( Tabein et al, 2020 ; Konakalla et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the studies on the topical application of dsRNA have been conducted against at least 14 plant viruses having positive sense ssRNA as their genome ( Taliansky et al, 2021 ). To some extent, the approach was also found to be effective against ssDNA virus (genus Begomovirus ), however, not much information is available as only three studies are available that showed limited or no effect against Begomovirus ( Namgiala et al, 2019 ; Rego-Machado et al, 2020 ; Melita et al, 2021 ). Recently, two studies had shown the efficacy of topically applied dsRNA against the type member of the genus Orthotospovirus , TSWV, a negative/ambisense ssRNA virus ( Tabein et al, 2020 ; Konakalla et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…RNAi has demonstrated its efficacy in silencing or suppressing the expression of critical genes in fungal pathogens. For example, studies have successfully deployed exogenous dsRNA to suppress fungal pathogens such as Fusarium o xysporum, bacterial pathogens such as Pectobacterium carotovorum , and viral pathogens such as tomato yellow leaf curl virus …”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have successfully deployed exogenous dsRNA to suppress fungal pathogens such as Fusarium oxysporum, 28 bacterial pathogens such as Pectobacte-rium carotovorum 29 , and viral pathogens such as tomato yellow leaf curl virus. 30 Fusarium head blight (FHB), caused by the pathogen F. graminearum, is a fungal disease of wheat that causes a reduction in the yield and quality of grains by producing mycotoxins. Fusarium species obtain nutrients from both living and dead tissues and are characterized as hemibiotrophic pathogens in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Topical dsRNA application also shows promise against monopartite geminiviruses such as Tomato yellow leaf curl virus (TYLCV) (56) and Chilli leaf curl virus (ChiLCV) (57).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the approach was successfully employed in blackgram plants against MYMV (55). Topical dsRNA application also shows promise against monopartite geminiviruses such as Tomato yellow leaf curl virus (TYLCV) (56) and Chilli leaf curl virus (ChiLCV) (57).…”
Section: Introductionmentioning
confidence: 99%